![4*log_{6}(3-\frac{3}{2x+3} ) =5*log_{6}(2+\frac{1}{x+1}) +4 4*log_{6}(3-\frac{3}{2x+3} ) =5*log_{6}(2+\frac{1}{x+1}) +4](https://tex.z-dn.net/?f=+4%2Alog_%7B6%7D%283-%5Cfrac%7B3%7D%7B2x%2B3%7D+%29+%3D5%2Alog_%7B6%7D%282%2B%5Cfrac%7B1%7D%7Bx%2B1%7D%29++%2B4+)
ОДЗ:
0 \atop {2+\frac{1}{x+1}}>0} \right. " alt=" \left \{ {{3-\frac{3}{2x+3}}>0 \atop {2+\frac{1}{x+1}}>0} \right. " align="absmiddle" class="latex-formula">
преобразуем логарифмируемые выражения:
1.
2. ![2+ \frac{1}{x+1}= \frac{2x+3}{x+1} 2+ \frac{1}{x+1}= \frac{2x+3}{x+1}](https://tex.z-dn.net/?f=2%2B+%5Cfrac%7B1%7D%7Bx%2B1%7D%3D+%5Cfrac%7B2x%2B3%7D%7Bx%2B1%7D+++)
3.
0} \atop {\frac{2x+3}{x+1}>0}} \right. " alt=" \left \{ {{6*\frac{x+1}{2x+3}>0} \atop {\frac{2x+3}{x+1}>0}} \right. " align="absmiddle" class="latex-formula">
=> x<-1,5. x>-1 ("не работают" математические символы, запишу неравенством)
уравнение:
![4*log_{6}(6*\frac{x+1}{2x+3})=5*log_{6}\frac{2x+3}{x+1}+4 4*log_{6}(6*\frac{x+1}{2x+3})=5*log_{6}\frac{2x+3}{x+1}+4](https://tex.z-dn.net/?f=+4%2Alog_%7B6%7D%286%2A%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%29%3D5%2Alog_%7B6%7D%5Cfrac%7B2x%2B3%7D%7Bx%2B1%7D%2B4+++++)
![4*(log_{6}6+log_{6}\frac{x+1}{2x+3})=5*log_{6} (\frac{x+1}{2x+3})^{-1}+4 4*(log_{6}6+log_{6}\frac{x+1}{2x+3})=5*log_{6} (\frac{x+1}{2x+3})^{-1}+4](https://tex.z-dn.net/?f=+4%2A%28log_%7B6%7D6%2Blog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%29%3D5%2Alog_%7B6%7D+%28%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%29%5E%7B-1%7D%2B4++++++)
![4*(1+log_{6}\frac{x+1}{2x+3})=5*(-1)*log_{6}\frac{x+1}{2x+3}+4 4*(1+log_{6}\frac{x+1}{2x+3})=5*(-1)*log_{6}\frac{x+1}{2x+3}+4](https://tex.z-dn.net/?f=+4%2A%281%2Blog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%29%3D5%2A%28-1%29%2Alog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%2B4+++++)
![4+4*log_{6}\frac{x+1}{2x+3}=-5*log_{6}\frac{x+1}{2x+3} +4 4+4*log_{6}\frac{x+1}{2x+3}=-5*log_{6}\frac{x+1}{2x+3} +4](https://tex.z-dn.net/?f=+4%2B4%2Alog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%3D-5%2Alog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D+++%2B4+++)
![9*log_{6}\frac{x+1}{2x+3}=0 9*log_{6}\frac{x+1}{2x+3}=0](https://tex.z-dn.net/?f=+9%2Alog_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%3D0+++)
![log_{6}\frac{x+1}{2x+3}=0 log_{6}\frac{x+1}{2x+3}=0](https://tex.z-dn.net/?f=+log_%7B6%7D%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%3D0+++)
![\frac{x+1}{2x+3}=6^{0} \frac{x+1}{2x+3}=6^{0}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%3D6%5E%7B0%7D+++)
![\frac{x+1}{2x+3}=1 \frac{x+1}{2x+3}=1](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%2B1%7D%7B2x%2B3%7D%3D1++)
=> x+1=2x+3
x = - 2
- 2 <- 1,5 (принадлежит ОДЗ)</p>
ответ: x = - 2